Hubungan Atribut Produk terhadap Keputusan Pembelian Beras Lokal Unggulan Kabupaten Mempawah - Wardani, Sri; Dolorosa, Eva; Kurniati, Dewi (Universitas Galuh, 2026)
Mempawah Regency possesses Superior Local Rice that serves as a prima donna. However, the threat of competition from imported rice competitors poses a challenge to the development of superior local rice. This research aims to analyze the relationship of product attributes to the purchasing decisions for Mempawah Regency's superior local rice. A descriptive qualitative approach is employed to explain the research findings, with 200 respondents analyzed using Spearman rank correlation. The research results indicate that all attribute variables of Mempawah Regency's superior rice are significantly correlated with purchasing decisions. The variables of Taste, Appeal, and Cleanliness attributes of the superior local rice exhibit a